2021
DOI: 10.1108/jsm-06-2020-0216
|View full text |Cite
|
Sign up to set email alerts
|

A typology of conspicuous donation on Facebook

Abstract: Purpose This study aims to present a typology of Facebook followers of charities, drawing on theories of value co-creation, impression management and conspicuous donation behavior. Design/methodology/approach Data from 234 students based in an Irish University and 296 adults in the USA were subjected to cluster analysis. Findings Four segments were identified, common to both samples. Quiet donors are less likely to engage with a charity on Facebook, yet they may donate to the charity. They follow a charity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…For example, Foth et al (2013) identified some blood donors prefer to be discrete and private with their donation decisions, while others wanted to conspicuously share their donation activity with others. Similarly, Wallace and Buil (2021) identified four segments of charity Facebook followers that varied in their likelihood to engage and highlight their good deeds to others. As such, the effects demonstrated in this study may be strengthened when donors receive their preferred format of donor appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Foth et al (2013) identified some blood donors prefer to be discrete and private with their donation decisions, while others wanted to conspicuously share their donation activity with others. Similarly, Wallace and Buil (2021) identified four segments of charity Facebook followers that varied in their likelihood to engage and highlight their good deeds to others. As such, the effects demonstrated in this study may be strengthened when donors receive their preferred format of donor appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fit of the measurement model, a cluster analysis was conducted per Punj and Stewart (1983). As this research seeks to better understand gig worker perceptions and performance, a cluster analysis was deemed the appropriate method of analysis (e.g., Wallace and Buil, 2021).…”
Section: Measurement Modelmentioning
confidence: 99%
“…Researchers have primarily focused on user-generated, characterized by conversations occurring naturally between individuals (Previte et al, 2019; Sundermann, 2018). Recently, Wallace and Buil (2021) identified four donor segments who varied by their “level of engagement” with charities on Facebook, “motivation to engage,” and “likelihood to donate” to the charity, with three of four segments willing to promote the charity online (e.g., via likes and mentions on Facebook). We argue that rather than relying on donors to naturally advocate for an NPO online, NPOs can cultivate such behavior through created “firm-generated” content that is sharable (Godes & Mayzlin, 2009; Kozinets et al, 2010).…”
Section: Defining Advocacymentioning
confidence: 99%
“…However, a lesser-known but emerging area of donor advocacy research involves examining the impact of sharing “firm-generated” content, such as a “virtual badge” (Chell et al, 2020). Simply, to encourage online advocacy by donors, NPOs may proactively create content for donors to use in their advocacy efforts, such as prepopulated tweets, “twibbons,” or a virtual badge of a donation activity (Chell & Mortimer, 2014; Wallace & Buil, 2021). Firm-generated virtual badges may include marketing messages that highlight an “individual’s contribution,” the “impact of their donation,” or a “call to action” (Chell & Mortimer, 2014).…”
Section: Hypothesis Developmentmentioning
confidence: 99%